2009
DOI: 10.4085/1062-6050-44.5.490
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Hip Muscle Function in Females With and Without Patellofemoral Pain Syndrome

Abstract: Context: Patellofemoral pain syndrome (PFPS) is a common knee condition in athletes. Recently, researchers have indicated that factors proximal to the knee, including hip muscle weakness and motor control impairment, contribute to the development of PFPS. However, no investigators have evaluated eccentric hip muscle function in people with PFPS.Objective: To compare the eccentric hip muscle function between females with PFPS and a female control group.Design: Cross-sectional study. Setting: Musculoskeletal lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 31 publications
1
55
0
5
Order By: Relevance
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…12,42,45,46 During weight-bearing activities, the hip must contract eccentrically to control the movement of the femur in the frontal and transverse planes. Decreased eccentric hip torque in individuals with PFPS has been reported, 7,10 but sex differences have not been investigated. Decreased hip muscle activation may also contribute to abnormal hip kinematics.…”
Section: T T Conclusionmentioning
confidence: 99%
“…Testing was performed at an angular speed of 30°/s. 10 All subjects received strong verbal encouragement during eccentric hip abduction and external rotation torque testing. The testing order was randomized to account for ordering bias.…”
Section: 35mentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired hip muscle performance is a common impairment observed in patients with PFP 1,5,17,25,27 and has been shown to be associated with altered hip kinematics in this population. 27,28 A recently published systematic review concluded that there is strong evidence that females with PFP demonstrate impaired strength of the hip musculature, as compared to control subjects.…”
Section: T T Conclusionmentioning
confidence: 99%